Socialization of Tempe for Household Industry Making in Indigenous Papua Communities in Malanu Malaimsimsa District, Sorong City, West Papua - Ibrahim Ibrahim (Pelita Eksakta, 2018)
The Socialization of Tempe production on Papua ethnic aimed to give some information of microorganism benefits in housing industry; to socialize the process of making Tempe; and to give suggestion to the society in order to use some certain microorganism in making their business. This study used library research; gave some information about the advantage of microorganism in making Tempe, how to product Tempe in housing scale. By the end of the presentation, it showed that most of Papua ethnic had no any experiences in making Tempe. It can be seen by their enthusiasm in attending the socialization and in learning how to make Tempe. Keywords — Socialization, Tempe Production, Papua Ethnic